2021
DOI: 10.3390/biology10030222
|View full text |Cite
|
Sign up to set email alerts
|

Post-Translational Protein Deimination Signatures in Plasma and Plasma EVs of Reindeer (Rangifer tarandus)

Abstract: The reindeer (caribou) Rangifer tarandus is a Cervidae in the order Artiodactyla. Reindeer are sedentary and migratory populations with circumpolar distribution in the Arctic, Northern Europe, Siberia and North America. Reindeer are an important wild and domesticated species, and have developed various adaptive strategies to extreme environments. Importantly, deer have also been identified to be putative zoonotic carriers, including for parasites, prions and coronavirus. Therefore, novel insights into immune-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 149 publications
(254 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, 85 arginines, potentially targets of deimination, are found in the 1699 aa protein sequence. This highlights that C3 is very likely to undergo deimination and C3 deimination was recently reported for the first time in teleost fish [ 23 ]; it has since been identified in a range of taxa including elasmobranchs [ 24 ], reptiles [ 25 ], birds [ 47 ], cetaceans [ 50 ], pinnipeds [ 51 ], and artiodactyls [ 52 , 53 ]. Furthermore, in teleost fish, C3 has been found in deiminated form in both serum as well as in serum EVs [ 44 , 46 ] and in mucosal EVs [ 42 ], while in the current study C3 was a deimination candidate in coelomic fluid only, but not in the EVs, while C3 was identified as part of the total proteomic cargo in the EVs.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Furthermore, 85 arginines, potentially targets of deimination, are found in the 1699 aa protein sequence. This highlights that C3 is very likely to undergo deimination and C3 deimination was recently reported for the first time in teleost fish [ 23 ]; it has since been identified in a range of taxa including elasmobranchs [ 24 ], reptiles [ 25 ], birds [ 47 ], cetaceans [ 50 ], pinnipeds [ 51 ], and artiodactyls [ 52 , 53 ]. Furthermore, in teleost fish, C3 has been found in deiminated form in both serum as well as in serum EVs [ 44 , 46 ] and in mucosal EVs [ 42 ], while in the current study C3 was a deimination candidate in coelomic fluid only, but not in the EVs, while C3 was identified as part of the total proteomic cargo in the EVs.…”
Section: Discussionmentioning
confidence: 93%
“…The KEGG pentose phosphate pathway was previously identified for deiminated proteins from cetacean sera [50] and in alveolates [31]. The biosynthesis of amino acids KEGG pathway was previously identified for deiminated proteins from bovine plasma and plasma-EVs [52], plasma and plasma-EVs of reindeer [53], naked mole-rats [48], and lampreys [41], from cetacean sera [50], and lobster haemolymph [39]. The fructose and mannose metabolism KEGG pathway was identified for deiminated proteins in cetacean sera [50], lamprey plasma [41], and in alveolates [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors do not comment on the role of the identified proteins in the pathogenesis of joint diseases. In addition, Marco Sancandi and Stefania D’Alessio showed the presence of a citrullinated form of the AMBP protein in pre-motor Parkinson’s disease and health assessment in animal models [ 57 , 58 ]. Using Western blotting methods and following-up LC-MS/MS analysis, Hoshimi Kawaguchi et al demonstrated the increased serum level of citrullatedAMBP protein in patients with RA.…”
Section: Discussionmentioning
confidence: 99%